Effect of low-dose ketamine on post-operative serum IL-6 production among elective surgical patients: a randomized clinical trial - Luggya, Tonny S.; Roche, Tony; Ssemogerere, Lameck; Kintu, Andrew; Kasumba, John M.; Kwizera, Arthur; Tindimwebwa, Jose V. B. (African Health Sciences, 2017)
Surgery and Anesthesia cause an excessive pro-inflammatory response. Mulago Hospital is faced with staff shortage making post-operative pain management difficult.Interleukin-6 (IL-6) drives inflammatory pain, endothelial cell dysfunction and fibrogenesis. Ketamine is cheap and, readily available. We hypothesized that its attenuation of serum IL-6 was a surrogate for clinical benefit. Materials and methods: Institutional Review Board’s approval was sought and RCT was registered at clinical trials.gov (identifier number: NCT01339065). Consenting patients were randomized to receive pre-incision intravenous ketamine - 0.5mg/kg or 0.9% saline placebo in weighted dosing. Blood samples were collected and laboratory analyzed at baseline, post-operatively in PACU, 24 and 48 hours respectively. Results: We recruited 39 patients of whom 18 were randomized to the ketamine arm and 21 in the placebo arm with follow up at 24 and 48 hours. Serum IL-6 and IL-1β levels were analyzed using ELIZA assay of pre-coated micro wells. Ketamine suppressed serum IL-6 at PACU with reduced increase at 24 hours. There was no reaction in 98% of IL-1β assayed. Conclusion: Low-dose ketamine attenuated early serum IL-6 levels due to surgical response with reduced 24 hour increase, but the difference was not statistically significant and we recommend more studies
Keywords: Ketamine; post-operative inflammation; interleukin 6